3D printing of stimuli-responsive hydrogel materials: Literature review and emerging applications - Arif, Zia Ullah; Khalid, Muhammad Yasir; Tariq, Ali; Hossain, Mokarram; Umer, Rehan (Giant (Oxford, England), 2024)
•Different types of stimuli-responsive hydrogels (SRHs) are reviewed.•Up-to-date usage of various 3D printing techniques for SRH-based structures is detailed.•The utilization of 3D-printed SRHs in different applications are highlighted.•Current challenges and future outlooks of SRHs are presented. Additive manufacturing (AM) aka three-dimensional (3D) printing has been a well-established and unparalleled technology, which is expanding the boundaries of materials science and is exhibiting an enormous potential to fabricate intricate geometries for healthcare, electronics, and construction sectors. In the contemporary era, the combination of AM technology and stimuli-responsive hydrogels (SRHs) helps to create dynamic and functional structures with extreme accuracy, which are capable of changing their shape, functional, or mechanical properties in response to environmental cues such as humidity, heat, light, pH, magnetic field, electric field, etc. 3D printing of SRHs permits the creation of on-demand dynamically controllable shapes with excellent control over various properties such as self-repair, self-assembly, multi-functionality, etc. These properties accelerate researchers to think of unthinkable applications. Additively manufactured objects have shown excellent potential in applications like tissue engineering, drug delivery, soft robots, sensors, and other biomedical devices. The current review provides recent progress in the 3D printing of SRHs, with more focus on their 3D printing techniques, stimuli mechanisms, shape-morphing behaviors, and their functional applications. Finally, current trends and future roadmap of additively manufactured smart structures for different applications have also been presented, which will be helpful for future research. This review holds great promise for providing fundamental knowledge about SRHs to fabricate structures for diverse applications. [Display omitted]